Effects of tannin source and concentration from tree leaves on two species of tadpoles. (3rd November 2014) - Earl, Julia E.; Semlitsch, Raymond D.
Abstract Vegetation in and around freshwater ecosystems can affect aquatic organisms through the production of secondary compounds, which are retained in leaves after senescence and are biologically active. Tannins can be toxic to tadpoles, but the plant source of tannins and tannin concentration have been confounded in experimental designs in previous studies. To examine the effects of the concentration and source of tannins (tree species), we examined the effects of 4 factors on tadpole survival, growth, and development: tannin source (red oak [Quercus rubra], white oak [Quercus alba], or sugar maple [Acer saccharum]); tannin concentration (including a control); diet protein level; and tadpole species (American toad [Anaxyrus americanus] and spring peepers [Pseudacris crucifer]). Tannin source and concentration affected spring peeper survival, but American toads had uniformly high survival. Spring peepers had a lower survival rate in high tannin concentrations of oak leachate but a high survival rate in both concentrations of sugar maple leachate. These differences in survival did not correspond with changes in dissolved oxygen, and no effect of dietary protein level on tadpole performance was observed. The presence of plant leachate resulted in increased tadpole growth in both species, but the mechanism for this finding is unclear. The results of the present study show that tannin concentration and source are important factors for tadpole performance, adding further evidence that plant chemistry can affect aquatic organisms. Environ Toxicol Chem 2015;34:120–126. © 2014 SETAC